2012
DOI: 10.1371/journal.pcbi.1002737
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing of Human Mitochondrial Reference Genomes Uncovers High Heteroplasmy Frequency

Abstract: We describe methods for rapid sequencing of the entire human mitochondrial genome (mtgenome), which involve long-range PCR for specific amplification of the mtgenome, pyrosequencing, quantitative mapping of sequence reads to identify sequence variants and heteroplasmy, as well as de novo sequence assembly. These methods have been used to study 40 publicly available HapMap samples of European (CEU) and African (YRI) ancestry to demonstrate a sequencing error rate <5.63×10−4, nucleotide diversity of 1.6×10−3 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 34 publications
2
54
0
1
Order By: Relevance
“…Among these 131 individuals, 24.43% were detected to possess heteroplasmy with MAF larger than 10% (13). Moreover, a study used a 454 Genome Sequencer FLX system and sequenced 40 HapMap individuals to a mean coverage of 120×, and 65% individuals were found to have heteroplasmies with MAF higher than 9% (14). With a MAF cutoff of 10%, the prevalence of heteroplasmy is 44.42% in our dataset (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Among these 131 individuals, 24.43% were detected to possess heteroplasmy with MAF larger than 10% (13). Moreover, a study used a 454 Genome Sequencer FLX system and sequenced 40 HapMap individuals to a mean coverage of 120×, and 65% individuals were found to have heteroplasmies with MAF higher than 9% (14). With a MAF cutoff of 10%, the prevalence of heteroplasmy is 44.42% in our dataset (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 78%
“…The advent of NGS technologies enables the inquiry of mitochondrial heteroplasmy at the genome-wide scale. Several studies using these approaches allowed detection of medium-and high-frequency heteroplasmy with minor allele frequency (MAF) higher than 9%, and it was found that 25∼65% of the general population have at least one heteroplasmy across the entire mitochondrial genome (12)(13)(14). However, deeper sequencing depth at the order of thousands is required for confident identification of low-frequency heteroplasmy (MAF in the range of 1%∼10%) (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TopHat option -read-mismatches was set to 2 and 3 (ie, allowing up to 2 and 3 mismatches in final read alignments), for CEU and YRI, respectively, because the mtDNA nucleotide diversity in YRI is higher than that in CEU. 15 By setting the TopHat option -g to 1, we deliberately allowed reads to be mapped on a single specific position on the genome. For each population, the expression values of log 10 (FPKM þ 1) for all genes were quantile-normalized across individuals.…”
Section: Estimation Of Transcript Abundancementioning
confidence: 99%
“…In cases where there is an abundance in the sample, for example mass graves in mass disasters, there are newly discovered forensically validated methods such as ESI-MS [22] Certainly, all such applications should have a strong grasp of the mtDNA variation that is present in the populations concerned. As an example, describing and frequency estimates of common mtDNA types and any population sub-structuring must be at hand [23]. Consequently, this may also increase the pool of samples with degraded and insufficient nuclear DNA for mitochondrial DNA analysis.…”
Section: Discussionmentioning
confidence: 99%